Hidden Voices of Japanese Returnees: The Quest for Identity and Life Trajectories - Firman Budianto (Humaniora, 2020)
The research aimed to discuss and analyze Japanese returnees’ life story and self-perception on their identity by emphasizing how the host country affected their identity development as well as their vision on the future. The data were drawn from in-depth interviews with three kikokushijo students and qualitatively analyzed. The research finds three areas related to how the host country shaped their identity and future life trajectory; the development of bicultural identity, the feeling of being kikokushijo in Japanese society nowadays, and the impact of living overseas to future life trajectory. Three kikokushijos in the research demonstrate the different processes in their bicultural identity formation. Among the key factors in such a process are the family and school. The social contexts of the country where they resided play a greater role not in shaping their cultural identity, but in shaping their life trajectories, particularly, their career aspirations and future mobility. However, the research suggests that the discourse on kikokushijo paves the way to the idea of individualism and heterogeneity in Japanese society.